SPE European Formation Damage Conference 2011
DOI: 10.2118/144248-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Clay Minerals' Effects on the Permeability Reduction in Water Injection Process in the Oil Fields

Abstract: Water availability for injection into oil reservoirs is an effective factor for superiority of water injection project. One of the parameters that cause undesirable effects on reservoir rock injectivity is clay minerals. The different structures of clay minerals will result in undesirable effects on rock permeability. Clay minerals enter into the pores and throats by injected water or they are a part of the structure of the reservoir rocks. Clay swelling from the viewpoint of the clay minerals type and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Drag forces are again determined by the flow velocity (Zeinijahromi et al, 2012) and pH value (Khilar & Fogler, 1998). pH of the carrier fluid can determine interfacial tension, the wettability of the rock and fine particles, then affect the detached force (Abbasi et al, 2011;Amaefule et al, 1987;Liu & Civan, 1995). Civan (2007) has investigated the critical velocity for different rocks, and the slowest critical velocity (at which detachment occurs due to viscous forces) is 0.01 cm/s while the velocity in this experiment is 0.008 cm/s; we can conclude that the velocity here is sufficiently slow to avoid particle detachment due to drag forces.…”
Section: 1029/2018jb017100mentioning
confidence: 99%
See 1 more Smart Citation
“…Drag forces are again determined by the flow velocity (Zeinijahromi et al, 2012) and pH value (Khilar & Fogler, 1998). pH of the carrier fluid can determine interfacial tension, the wettability of the rock and fine particles, then affect the detached force (Abbasi et al, 2011;Amaefule et al, 1987;Liu & Civan, 1995). Civan (2007) has investigated the critical velocity for different rocks, and the slowest critical velocity (at which detachment occurs due to viscous forces) is 0.01 cm/s while the velocity in this experiment is 0.008 cm/s; we can conclude that the velocity here is sufficiently slow to avoid particle detachment due to drag forces.…”
Section: 1029/2018jb017100mentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) injection into deep saline aquifers is currently considered the best solution for reducing CO 2 emissions into the atmosphere and to thus mitigate climate change (Bachu, 2015;Iglauer et al, 2016;Nordbotten et al, 2005). It is well established that fine particles present in the sandstone can be released and mobilized (Alvarez et al, 2006;Bedrikovetsky et al, 2012;Civan, 2010;Gruesbeck & Collins, 1982;Lemon et al, 2011;Qajar et al, 2012;Abbasi et al, 2011); fine particles are usually located on the surface of rock grain. Such fines can also subsequently reattach onto other particles (Bertos et al, 2004;Wigand et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Swelling of clays may occur at different stages of drilling, hydraulic fracturing, or production, which not only damages cementing quality and petrophysical logging records but also in a larger view shortens the lifetime of the borehole and causes great expenses [4]. With regard to the fluid flow, the clay-caused challenges usually include migration and concentration of clay in the pore throats, and damaging the permeability [2,5,6]. Therefore, understanding the detailed properties of the clay minerals in the hydrocarbon reservoir is of benefit for all drilling, well logging, and reservoir engineers.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized, at the laboratory-scale measurements and those obtained on petroleum deposits, that oil wells have low injectivities with respect to water as a result of the presence of clays. For this reason, the presence of clay in the sandstone reservoirs is critical during secondary recovery operations by water. Subsequent work has shown that the presence of clays in petroleum reservoirs can have the following effects: the permeability during the secondary recovery operation with water is lower than that of air permeability; reduction of the permeability will not occur immediately in the waterflooding process; and the ionic concentration of water greatly affects the reduction of the permeability. , Because of the influence of clay on permeability, the water relative permeability and the displacement of the oil by water can be expected to be affected to a large extent by the presence of clays. In addition, the water/oil relative permeability curves may also be affected by the injection pressure, the pressure gradient, and the gravitational gradient that may decrease the capillary forces; the relative permeability trend is strongly dependent upon the invaded phase as well-demonstrated in the work of Akbarabadi and Piri, in which brine relative permeability of the drainage process initially exhibits a very rapid decline followed by a gradual reduction with a decrease in brine saturation.…”
Section: Introductionmentioning
confidence: 99%